2008
DOI: 10.1136/jnnp.2007.114595
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive complaints in the early phase after stroke are not indicative of cognitive impairment

Abstract: Cognitive complaints hindering daily life are frequently reported in the early weeks after stroke but are no indication for impaired cognitive performance. To identify patients with cognitive impairment, neuropsychological assessment is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
69
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 30 publications
9
69
2
1
Order By: Relevance
“…4 In addition, no association between SCF and cognitive performance was found in patients with stroke. 3,5 It is possible that this association is only apparent in healthy people, without a preceding symptomatic event, such as a stroke. This might reduce the occurrence of problems in adjustment, such as anxiety and depression, after an event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In addition, no association between SCF and cognitive performance was found in patients with stroke. 3,5 It is possible that this association is only apparent in healthy people, without a preceding symptomatic event, such as a stroke. This might reduce the occurrence of problems in adjustment, such as anxiety and depression, after an event.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship with objective cognitive performance on neuropsychological assessment is unclear. Although most studies showed no relationship with objective cognitive impairment when corrected for mood and health, [1][2][3][4][5][6] some studies reported positive associations. 7,8 However, studies have shown a strong association with poor physical health 6 and depression.…”
mentioning
confidence: 99%
“…In the past decades, the neuropsychological literature has consistently reported that cognitive impairment is commonly observed after stroke and might affect up to 50% of stroke patients (e.g., Duits et al, 2008). This finding is reason for concern, as the presence of cognitive impairment has been associated with a negative influence on the outcome as well as with significant functional problems in daily life (e.g., Galski et al, 1993;Zinn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is reason for concern, as the presence of cognitive impairment has been associated with a negative influence on the outcome as well as with significant functional problems in daily life (e.g., Galski et al, 1993;Zinn et al, 2004). It is thus vitally important to adequately assess cognitive problems after stroke, given that the information obtained from the assessment can contribute to the rehabilitation treatment, for instance in establishing the treatment strategy or in providing advice to patients and their caregivers (Duits et al, 2008). It should, however, also be noted that an extensive cognitive assessment is a rather costly and time-consuming procedure that might not be required for all stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…These complaints occur early after stroke and often remain present until years after the event (Carlsson, Moller, & Blomstrand, 2003;Duits, Munnecom, van Heugten, & van Oostenbrugge, 2008;Nijsse et al, 2017;Wendel, Risberg, Pessah-Rasmussen, Stahl, & Iwarsson, 2008). The most commonly reported SCC in this population include mental slowness, concentration difficulties and memory problems (van Rijsbergen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%